John-Teller Distortion in Octahedral hexaaquacopper (II) Transition for S=1/2, d9 Metal Complex (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2022)
Jahn–Teller effect (JTE) describe how specific electrons distributions induce geometric deformation in molecules or ions. The distortion of Jahn–Teller (JT) takes place because of the uneven occupation of orbitals with the identical energies is disapproving. To prevent such inappropriate electronic arrangements, molecules distort (lose regularity), causing these orbitals to become non-degenerate. This distortion is most frequently seen in octahedral compounds, at which two axial bonds could be squeezed (compressed) or extend (elongated), leading to bond lengths that the different from equator bonds. The degeneracy of electronic states really isn’t accurately measured, but it would be measured precisely by the disparity in a concentration of electron among metal and the ligands upon on axil direction. The density functional theory has been used to calculate bond length in both cases  geometry for ,  octahedral metal-complexes, the majority ordinary mechanism of distortion is elongation (z-out). In perfectly octahedral complexes deformation, the  orbitals energy is changed more than the  orbitals energy, causing elongation z-out distortion. The d-levels energy would be splitting in a ligand field throughout transition metal centers can frequently result in degenerate electron configurations that are subject to Jahn–Teller effects. In six-coordinate complexes of copper II ions. It is also significant in fewer regular oxidation levels of other transition ions with that  count.